PENGGUNAAN BAHASA DAERAH (SUNDA) DI KALANGAN REMAJA DALAM MELESTARIKAN BAHASA NASIONAL UNTUK MEMBANGUN JATI DIRI BANGSA - S N M Aljamaliah; D M Darmadi (Universitas Wijaya Kusuma Surabaya, 2021)
The use of language is the most important part of communication. Without using language, communication between humans cannot be done. Indonesia is a country that has various ethnic groups, cultures, languages, races and religions. Based on this, of course, in Indonesia there are various kinds of regional languages. One of the regional languages is Sundanese which is used by the Sundanese. This study aims to preserve the local language (Sundanese) among teenagers. This research uses a case study method with a qualitative approach, this research is carried out by exploring and describing the phenomena that occur. The current phenomenon is that teenagers who are local language maintainers have started to rarely use local languages. The position of regional languages has decreased, including the use of Sundanese. This can be influenced by the use of a second language, both Indonesian and foreign languages. Teenagers think that Indonesian and foreign languages have a more prestigious position than regional languages. Therefore, the use of Sundanese is considered important with a view to preserving and maintaining the Sundanese language.